Phenotypic diversity and pattern of variation in West African plantains (Musa spp. AAB group) - Swennen, Rony L.; Vuylsteke, D.R.; Ortíz, R. (1995)
Plantains (Musa spp., AAB group) are an important food crop and an integral component of the farming systems in the lowland humid forest zone of West and Central Africa. A group of 24 plantain cultivars, representing the major variability in West Africa, was evaluated for nine quantitative characters. The association between growth and yield parameters in this African plantain germplasm was examined to determine if the pattern of quantitative variation in inflorescence and vegetative traits agreed with taxonomic groupings based on inflorescence type and plant size. Phenotypic correlations between these traits were calculated. Giant cultivars were taller, their pseudostem thicker, and they flowered much later than medium-sized cultivars. Giant cultivars produced more foliage, resulting in heavier bunches with more hands and fruits. Groupings that resulted following principal component analysis (PCA) supported conventional taxonomic groupings of plantains. PC A was based mainly on time to flowering, pseudostem height, and number of fruits. The last two traits, in combination with the number of hermaphrodite flowers and the persistence of the male bud, sufficed to group plantain cultivars